Highly Sensitive Whole-Cell Biosensor for Cadmium Detection Based on a Negative Feedback Circuit - Zhang, Guangbao; Hu, Shuting; Jia, Xiaoqiang (Frontiers in Bioengineering and Biotechnology, 2021)
Although many whole-cell biosensors (WCBs) for the detection of Cd2+ have been developed over the years, most lack sensitivity and specificity. In this paper, TCM was developed in P. putida KT2440 as a Cd2+ WCB with a negative feedback amplifier. Based on the slope of the linear detection curve as a measure of sensitivity, the negative feedback amplifier in TCM greatly increased the output signal of the reporter mCherry, resulting in 33% greater sensitivity than in an equivalent WCB without the negative feedback circuit, named CM. Moreover, TCM exhibited increased Cd2+ tolerance and a lower detection limit of 0.1 nM, a remarkable 400-fold improvement compared to the biosensor CM, which is significantly below the WHO standard of 27 nM (0.003 mg/L) for cadmium in drinking water. Due to the superior amplification of the output signal, TCM can provide a detectable signal in a much shorter time, and a fast response is highly preferable for real field applications. In addition, the biosensor TCM with negative feedback amplifier showed an unusually high specificity for Cd2+ compared to other metal ions, giving signals with other metals that were between 17.6 and 41.4 times weaker than with Cd2+. In summary, the negative feedback amplifier WCB designed in this work meets the requirements of Cd2+ detection with very high sensitivity and specificity, which also demonstrates that genetic negative feedback amplifiers are excellent tools for improving the performance of WCBs.